Ensemble characterization of an intrinsically disordered FG‐Nup peptide and its F>A mutant in DMSO‐d6. Issue 6 (22nd July 2017) - Reid, Korey M.; Sunanda, Punnepalli; Raghothama, S.; Krishnan, V.V.
Abstract: Intrinsically disordered proteins (IDP) lack a well‐defined 3D‐structure under physiological conditions, yet, the inherent disorder represented by an ensemble of conformation plays a critical role in many cellular and regulatory processes. Nucleoporins, or Nups, are the proteins found in the nuclear pore complex (NPC). The central pore of the NPC is occupied by Nups, which have phenylalanine‐glycine domain repeats and are intrinsically disordered, and therefore are termed FG‐Nups. These FG‐domain repeats exhibit differing cohesiveness character and differ from least (FG) to most (GLFG) cohesive. The designed FG‐Nup is a 25 AA model peptide containing a noncohesive FG‐motif flanked by two cohesive GLFG‐motifs (WT peptide). Complete NMR‐based ensemble characterization of this peptide along with a control peptide with an F>A substitution (MU peptide) are discussed. Ensemble characterization of the NMR‐determined models suggests that both the peptides do not have consistent secondary structures and continue to be disordered. Nonetheless, the role of cohesive elements mediated by the GLFG motifs is evident in the WT ensemble of structures that are more compact than the MU peptide. The approach presented here allows an alternate way to investigate the specific roles of distinct amino acid motifs that translate into the long‐range organization of the ensemble of structures and in general on the nature of IDPs. Abstract :